VASYL STEFANYK AND HRYHORIY KOSYNKA: THE ISSUE OF CRIME IN THE CONTEXT OF THE PAST AND THE PRESENT (COMPARATIVE ASPECT OF THE WRITTER’S CREATIVE - Senyk, L. T. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The paper examines crime as a theme in belles lettres and as socio-political reality in the context of past and contemporary realia. The affinity of writers is determined by the elements of style and the world outlook of difficult, tragic man-breaks in the late 19th as well as pollowing decades of the 209th century. The originality of artistic interpretation, expressivity of the “condensed” text, subtle psychologism, “hidden” philosophicity reveal their creative personalities and innovative identities.